an J Health Educ Health Promot 2018
DOI: 10.30699/acadpub.ijhehp.6.2.95
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Police-Assistant Students Compared with the Other Students in Schools of Hamadan, Concerning the Prevention of Road Traffic Injuries

Abstract: Background and Objective: one of the major causes of child mortality is road traffic injuries. Police-assistant students are the students, who receive education on basic and simple contents of road traffic incidents. This study was conducted in order to investigate the performance of police-assistant male students comparing with the other students in Hamadan, concerning the prevention of road traffic injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Many studies have shown that this theory could be applied to the prediction of traffic intention and behavior. 10 - 12 …”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that this theory could be applied to the prediction of traffic intention and behavior. 10 - 12 …”
Section: Introductionmentioning
confidence: 99%